PERAN ORANG TUA PEMULUNG MENUNJANG PENDIDIKAN FORMAL ANAK DI TPA SAMPAH KELURAHAN BATULAYANG - Yasma, Anggun; Salim, Izhar; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aimed to find out the role of scavenger parentsin supporting formal education in children (Study in the Landfill in Kelurahan Batulayang). The method used was a qualitative method with descriptive analysisand the technique of data collection for observation, interviews and documentation study. The results of this study showed that the role of parents in giving the formal education for children has been done. This was proven by the scavenger family at Landfill in Kelurahan Batulayang 1) The Role of Scavenger Parents as Motivator, Parents played a role in encouraging their children to be directedand enthusiastic to go to school by helping, supervising, and giving the direction when children are at home. 2) The role of Scavenger Parents as Facilitator was also done, by fulfilling the needs and school supplies for their children, they know the development of facilities that must be fulfilled by asking the teacher of their children, and the needsin supporting the formal education of children has been fulfilled. 3) The Role of Scavenger Parents as Mediators, namely their parents maintainedthe communication with their childrenso that the childrenwere open to sharing their activities and problems with both the teacher or their friends, so that parents easily become mediators in overcoming all their children's problems. Â Keywords: The Role of Parents, Scavenger Parents, Landfill in Kelurahan Batulayang